SINIF I VE II HLA ANTiJENLERi iLE SARKOiDOZ ARASINDAKi İLİŞKİNİN ARAŞTIRILMASI - ERDOĞAN, Ergun; KARAYEL, Tuncer; DEMİRCİ, Sabriye and ÇAĞATAY, Tülin and YANARDAĞ, Halil and MİDİLLİ, Kenan and YILMAZ, Erkan and SİPAHİ DEMİRKÖK, Sevtap and BİLİR, Muammer (Cerrahpaşa Medical Journal, 2019)
Background and Design.- There are sewral reports suggesting an association between certain human leukocyte antigents (HLA) and sarcoidosis. In different races, different HLA antigens were found more frequent in sarcoidosis patients compared to the controls. Results and Conclusion.- Thirty eight sarcoidosis patients with pulmonary and extrapulmonary in(31 female and 7 male, mean age 38±16.1) were included to the study. PA chest-x ray examinations rewaled that 13 patients had radiological stage I, 21 stage II and 4 stage Ill disease. An historical control group consisting of 160 kidney donor candidates was used as control group. HLA-A, HLA-B, HLA-DL and HLA-DQ antigens were determined by lymphocytotoxicity assay. The frequencies of HLA-A2, -BB, - 822, -838, -DR4 and DR14 were significantly higher in sarcoidosis patients (OR values 3.36, 5.42; 14.8, 29.81, 5.35 and 14.81, respectiwly) compared to the control group. There were no associations between radiological stage and time of onset of the disease, therapeutic response to corticosteroids, but the frequency of HLA-A2 in patients with pulmonary inand HLA-838 in patients with extrapulmonary inwas higher.